AN EXTENDED OCTAGONAL RING DYNAMOMETER FOR MEASUREMENT OF FORCES ON A SIMPLE TILLAGE TOOL (Nigerian Journal of Technology, 2003)
The analysis, design, construction, evaluation and use of an extended octagonal ring dynamometer for measurement of draught, vertical force and moment on a simple tillage tool are presented. The dynamometer was used to measure tool forces as functions of depth, rake angle and speed, for a wide plane blade. The dynamometer was designed for a maximum draught of 4.4 kN, vertical force of 4.0 kN and moment of 2.2 kN-m. Evaluation and calibration showed linear response (R2 =  0.99 to 1.00) for the relationship between applied load and output voltage and no hysteresis effect within the load range was observed. Actual sensitivity obtained were 0.332 m V/N.V for draught, 0.726m V/N.V for vertical force and 2.5 m V/N-m.V for moment. Maximum cross sensitivity was less than 6%. The dynamometer showed expected response of tool forces as affected by tool depth, rake angle and speed.